Methodology of Vector-Contextual Approach in Post-Non-Classical Science and Education - A G Madzhuga; I A Sinitsyna (Peoples' Friendship University of Russia (RUDN University), 2014)
This article examines the theoretical and methodological foundations of the new approach to psychological and educational research, the vector-contextualized approach, reveals its essence. The scientific principles underlying the vector-contextual approach are scientifically substantivated. It presents the comparative analysis of the environmental, vector-contextualized and synergistic approaches and shows their role in the post-non-classical scientific knowledge.